Comparison of the Effects of Myofascial Meridian Stretching Exercises and Acupuncture in Patients with Low Back Pain - Dilek Eker Büyükşireci; Nesrin Demirsoy; Setenay Mit; Ersel Geçioğlu; İlknur Onurlu; Zafer Günendi (Medical Association of Pharmacopuncture Institute, 2022)
Background : Acupuncture and myofascial meridians show great anatomical and clinical compatibility. Objectives: We aimed to compare the effects of myofascial meridian stretching exercises and acupuncture in patients with low back pain. Methods : We randomized 81 subjects with acute/subacute low back pain into three groups: an acupuncture (A) group, a myofascial meridian stretching (MMS) group, and a control (C) group. We recorded the Numerical Rating Scale (NRS) and Roland- Morris Disability Questionnaire (RMQ) scores at baseline and weeks two and six. We evaluated posterior pelvic tilt and transversus abdominis muscle strenghth with a pressure biofeedback unit, back extensor muscle strength by the Sorenson test, and lumbar range of motion (ROM) with an inclinometer. Group A received acupuncture (BL 57 and BL 62 acupoints) and stretching exercises according to the posterior superficial line were applied to the MMS group. Results : Improvements in the NRS score were more prominent in group A than in group C (p = 0.004). The RMQ score improvement between baseline and weeks two and six was more prominent in groups A and MMS (p < 0.001, p = 0.001, respectively). The Sorenson test showed significant improvement between the baseline and week two in groups A and MMS (p = 0.004, p < 0.001, respectively). The increase in lumbar ROM measurement in the MMS group between baseline and week two was significantly higher than in groups A and C (p = 0.009, p < 0.001, respectively). Conclusion : Stretching exercises according to the myofascial meridian system and acupuncture contributed to improved symptoms in the first two weeks in patients with acute/subacute low-back pain.